Electrostatic image developing carrier, electrostatic image developer, image forming method, and image forming apparatus
The electrostatic image developing carrier, featuring magnetic particles and a resin layer with optimized silica particle sizes and Si element ratios, addresses the issue of image dropout in high temperature and high humidity environments by enhancing abrasion resistance and charge suppression.
Patent Information
- Application Number
- JP2021087895
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-25
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-05-25
AI Technical Summary
Existing electrostatic image developing carriers fail to prevent image dropout when high-density images are formed continuously in high temperature and high humidity environments, especially after a sequence of low image density images are printed.
A carrier for developing electrostatic images is designed with magnetic particles and a resin layer containing silica particles with an average particle diameter of 50 nm to 200 nm. The Si element ratios in specific regions of the resin layer and magnetic particles are optimized to satisfy certain equations, enhancing abrasion resistance and charge suppression.
The proposed carrier effectively suppresses image loss by improving abrasion resistance and preventing charge injection during toner development, even under harsh high temperature and high humidity conditions.
Smart Images

Figure 0007669801000003 
Figure 0007669801000004 
Figure 0007669801000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrostatic image developing carrier, an electrostatic image developer, an image forming method, and an image forming apparatus. [Background technology]
[0002] Patent Document 1 proposes a carrier for developing electrostatic images, comprising: a carrier body having a core material and a coating resin layer coating the core material; and spherical silica particles having a volume average particle size of 50 nm or more and 300 nm or less, the particles adhering to a surface of the carrier body in an amount of 0.001 part by mass or more and 0.100 part by mass or less per 100 parts by mass of the carrier body. Patent Document 2 proposes "an electrostatic latent image developing carrier having a core material coated with a resin, the carrier having a resin layer composed of at least three resins: a curable resin containing a triazine ring, a crosslinking agent that crosslinks the curable resin, and a non-crosslinkable fluorine-containing resin." [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-186005 A [Patent Document 2] Japanese Patent Application Publication No. 09-319155 Summary of the Invention [Problem to be solved by the invention]
[0004] The object of the present invention is to provide an electrostatic image developing carrier having magnetic particles and a resin layer that covers the magnetic particles and contains silica particles with an average particle size of 50 nm or more and 200 nm or less, in which the ratio Si1 of Si elements in a region where the distance from the surface of the resin layer in the direction toward the inside is 0.1 μm or more and 0.2 μm or less, and the ratio Si2 of Si elements in a region where the distance from the surface of the magnetic particles in the direction toward the surface of the resin layer is 0.0 μm or more and 0.1 μm or less, satisfy the following formula C1-1 or the following formula C2-1, and suppress the occurrence of image voids when a high-density image is formed in a high-temperature, high-humidity environment after successively forming low-density images in a high-temperature, high-humidity environment, compared to when the ratio Si1 of Si elements in a region where the distance from the surface of the magnetic particles in the direction toward the surface of the resin layer satisfies the following formula C1-1 or the following formula C2-1: Formula C1-1: 0.005>Si1 or Si1>2 Formula C2-1: 1>Si1 / Si2 or Si1 / Si2>1000 [Means for solving the problem]
[0005] The above problems are solved by the following means: <1> Magnetic particles; a resin layer that covers the magnetic particles and contains silica particles having an average particle size of 50 nm or more and 200 nm or less; The carrier for developing electrostatic images, wherein a ratio Si1 of the Si element in a region where the distance from the surface of the resin layer in the direction toward the inside is 0.1 μm or more and 0.2 μm or less, and a ratio Si2 of the Si element in a region where the distance from the surface of the magnetic particle in the direction toward the surface of the resin layer is 0.0 μm or more and 0.1 μm or less, satisfy the following formula 1-1 and the following formula 2-1. Formula 1-1: 0.005≦Si1≦2 Formula 2-1:1≦Si1 / Si2≦1000 <2> The ratio Si1 satisfies the following formula 1-2: <1> 2. The electrostatic image developing carrier according to claim 1 . Formula 1-2: 0.01≦Si1≦1 <3> The ratio Si1 and the ratio Si2 satisfy the following formula 2-2: <2> 2. The electrostatic image developing carrier according to claim 1 . Formula 2-2: 50≦Si1 / Si2≦400 <4> The magnetic particles have an arithmetic surface roughness Ra of 0.2 μm≦Ra≦2 μm. <1> ~ <3> 10. The electrostatic image developing carrier according to claim 9, <5> The silica particles have an average particle size of 55 nm or more and 150 nm or less. <1> ~ <4> 10. The electrostatic image developing carrier according to claim 9, <6> The thickness of the resin layer is 0.3 μm or more and 3.0 μm or less. <1> ~ <5> 10. The electrostatic image developing carrier according to claim 9, <7> The above <1> ~ <6> 2. An electrostatic image developer comprising the electrostatic image developing carrier and the electrostatic image developing toner according to claim 1. <8> a charging step of charging at least an image carrier; an exposure step of forming an electrostatic latent image on the surface of the image carrier; a developing step of developing the electrostatic latent image formed on the surface of the image carrier with an electrostatic charge image developer to form a toner image; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a transfer receiving material; a fixing step of fixing the toner image, The electrostatic image developer is <7> The electrostatic image developer according to claim 1, Image forming method. <9> An image carrier; A charging means for charging the image carrier; an exposure means for exposing the charged image carrier to light to form an electrostatic latent image on the image carrier; a developing means for developing the electrostatic latent image with an electrostatic charge image developer to form a toner image; a transfer means for transferring the toner image from the image carrier to a transfer medium; A fixing unit for fixing the toner image, The electrostatic image developer is <7> The electrostatic image developer according to claim 1, Image forming device. Effect of the Invention
[0006] <1> According to the invention, there is provided an electrostatic image developing carrier having magnetic particles and a resin layer covering the magnetic particles and containing silica particles with an average particle size of 50 nm or more and 200 nm or less, in which the ratio Si1 of Si element in a region where the distance from the surface of the resin layer in the direction toward the inside is 0.1 μm or more and 0.2 μm or less, and the ratio Si2 of Si element in a region where the distance from the surface of the magnetic particles in the direction toward the surface of the resin layer is 0.0 μm or more and 0.1 μm or less, satisfy the following formula C1-1 or the following formula C2-1, which suppresses the occurrence of image voids when a high-density image is formed in a high-temperature, high-humidity environment after successively forming low-density images in a high-temperature, high-humidity environment, compared to when the ratio Si1 of Si element in a region where the distance from the surface of the magnetic particles in the direction toward the surface of the resin layer satisfies the following formula C1-1 or the following formula C2-1. Formula C1-1: 0.005>Si1 or Si1>2 Formula C2-1: 1>Si1 / Si2 or Si1 / Si2>1000 <2> According to the invention, there is provided a carrier for developing electrostatic images which suppresses the occurrence of image voids when a high-density image is formed under a high-temperature, high-humidity environment after successively forming low-density images under a high-temperature, high-humidity environment, compared to the case where the ratio Si1 satisfies the following formula C1-2. Formula C1-2: 0.01>Si1 or Si1>1 <3> According to the invention, there is provided a carrier for developing electrostatic images which suppresses the occurrence of image voids when a high-density image is formed under a high-temperature, high-humidity environment after successively forming low-density images under a high-temperature, high-humidity environment, compared to the case where the ratio Si1 and the ratio Si2 satisfy the following formula C2-2. Formula C2-2: 50>Si1 / Si2 or Si1 / Si2>400 <4> According to the invention, there is provided a carrier for developing electrostatic images which suppresses the occurrence of image voids when a high density image is formed under a high temperature and high humidity environment after successively forming low image density images under a high temperature and high humidity environment, compared to when the arithmetic surface roughness Ra of the surface of the magnetic particle is 0.2 μm>Ra or Ra>2 μm. <5> According to the present invention, there is provided a carrier for developing electrostatic images which suppresses the occurrence of image voids when a high density image is formed under a high temperature and high humidity environment after successively forming low image density images under a high temperature and high humidity environment, as compared to when the average particle size of the silica particles is less than 55 nm or exceeds 150 nm. <6> According to the present invention, there is provided a carrier for developing electrostatic images which suppresses the occurrence of image voids when a high density image is formed under a high temperature and high humidity environment after successively forming low image density images under a high temperature and high humidity environment, compared to when the thickness of the resin layer is less than 0.3 μm or exceeds 3.0 μm. <7> , <8> or <9> According to the invention, there is provided an electrostatic image developer, an image forming method, or an image forming apparatus including an electrostatic image developing carrier having magnetic particles and a resin layer covering the magnetic particles and containing silica particles with an average particle size of 50 nm or more and 200 nm or less, in which the ratio Si1 of Si element in a region where the distance from the surface of the resin layer toward the inside is 0.1 μm or more and 0.2 μm or less, and the ratio Si2 of Si element in a region where the distance from the surface of the magnetic particles toward the surface of the resin layer is 0.0 μm or more and 0.1 μm or less, satisfy the above formula C1-1 or the above formula C2-1, which suppresses the occurrence of image voids when a high density image is formed under a high temperature and high humidity environment after successively forming low image density images under a high temperature and high humidity environment, compared to when the ratio Si1 of Si element in a region where the distance from the surface of the magnetic particles toward the surface of the resin layer satisfies the above formula C1-1 or C2-1. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of an image forming apparatus that can be suitably used in the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge that can be suitably used in the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described as an example. The description and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the present invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0009] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if the composition contains multiple substances corresponding to each component, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.
[0010] <Electrostatic image developing carrier> The carrier for developing electrostatic images (hereinafter also referred to as "carrier") according to this embodiment has magnetic particles and a resin layer that covers the magnetic particles and contains silica particles having an average particle size of 50 nm or more and 200 nm or less. In addition, the ratio Si1 of Si elements in a region where the distance from the surface of the resin layer toward the inside is 0.1 μm or more and 0.2 μm or less, and the ratio Si2 of Si elements in a region where the distance from the surface of the magnetic particle toward the surface of the resin layer is 0.0 μm or more and 0.1 μm or less, satisfy the following formula 1-1 and the following formula 2-1. Formula 1-1: 0.005≦Si1≦2 Formula 2-1:1≦Si1 / Si2≦1000
[0011] The carrier according to the present embodiment, with the above-mentioned configuration, suppresses the occurrence of image omissions when forming a high-density image (e.g., an image with an image density of 30% or more) in a high-temperature, high-humidity environment (e.g., an environment of 28.5°C and 85% RH) after successively forming low-density images (e.g., images with an image density of 1% or less) in a high-temperature, high-humidity environment (e.g., an environment of 28.5°C and 85% RH).The reason for this is presumed to be as follows.
[0012] Continuous formation of low density images in a high temperature and humidity environment may cause wear of the resin layer of the carrier. This may lead to an irregular structure of the developing brush formed on the developing sleeve and to which the developer consisting of the carrier and the toner is attached. If the structure of the developing brush becomes irregular, when forming a high density image in a high temperature and humidity environment, electric charges are easily injected into the carrier during toner development, which may cause image omissions. Note that when a colored image is formed on white paper and image omissions occur, the image omissions are called white spots.
[0013] In the carrier according to the present embodiment, the ratio Si1 satisfies the above formula 1-1. By making the ratio Si1 0.005 or more, the amount of silica particles near the carrier surface increases, thereby improving the wear resistance of the carrier. In addition, by making the ratio Si1 2 or less, the amount of silica particles near the carrier surface is not too large, and the reduction in the resistance of the carrier caused by the inclusion of silica particles is suppressed, and the injection of charges into the carrier during toner development is easily suppressed. Furthermore, by making the ratio Si1 and the ratio Si2 satisfy the above formula 2-1, a large number of silica particles are present near the carrier surface, which makes it easier to improve the wear resistance of the carrier. Therefore, the carrier according to the present embodiment is less susceptible to wear and the structure of the developing brush is less likely to become irregular, even when low density images are continuously formed in a high temperature and high humidity environment. As a result, the injection of electric charges into the carrier during toner development is suppressed.
[0014] From the above, it is presumed that the carrier of this embodiment, due to the above-mentioned configuration, suppresses the occurrence of image omissions when a high-density image is formed in a high-temperature, high-humidity environment after successively forming low-density images in a high-temperature, high-humidity environment.
[0015] (magnetic particles) The magnetic particles are not particularly limited, and known magnetic particles used as the core material of carriers are applied.Specific examples of the magnetic particles include magnetic metal particles such as iron, nickel, and cobalt; magnetic oxide particles such as ferrite and magnetite; resin-impregnated magnetic particles in which porous magnetic powder is impregnated with resin; magnetic powder-dispersed resin particles in which magnetic powder is dispersed and mixed in resin; and the like.In this embodiment, the magnetic particles are preferably ferrite particles.
[0016] The volume average particle size of the magnetic particles is preferably from 15 μm to 100 μm, more preferably from 20 μm to 80 μm, and even more preferably from 30 μm to 60 μm. The volume average particle size herein means a particle size D50v that is 50% cumulative from the small diameter side in a volume-based particle size distribution.
[0017] The arithmetic surface roughness Ra (JIS B0601:2001) of the surface of the magnetic particle is preferably 0.2 μm or more and 2 μm or less, and more preferably 0.4 μm or more and 1.3 μm or less. By setting the arithmetic surface roughness Ra of the magnetic particle surface within the above range, the wear resistance of the carrier is improved, and therefore, image voids are more effectively prevented when a high density image is formed in a high temperature and high humidity environment after successively forming low density images in a high temperature and high humidity environment. The arithmetic surface roughness Ra of the magnetic particle surface is determined by observing the magnetic particle at an appropriate magnification (e.g., 1000x magnification) using a surface shape measuring device (e.g., Keyence Corporation's "Ultra-Deep Color 3D Shape Measuring Microscope VK-9700"), obtaining a roughness curve at a cutoff value of 0.08 mm, and extracting a reference length of 10 μm from the roughness curve in the direction of the average line. The Ra of 100 magnetic particles is calculated as the arithmetic average.
[0018] The magnetic force of the magnetic particles is preferably 50 emu / g or more, more preferably 60 emu / g or more, in terms of saturation magnetization in a magnetic field of 3000 oersteds. The saturation magnetization is measured using a vibrating sample magnetic measuring device VSMP10-15 (manufactured by Toei Kogyo Co., Ltd.). The measurement sample is packed in a cell with an inner diameter of 7 mm and a height of 5 mm and set in the device. The measurement is performed by applying a magnetic field and sweeping up to a maximum of 3000 oersteds. The applied magnetic field is then reduced, and a hysteresis curve is prepared on a recording paper. The saturation magnetization, residual magnetization, and retentivity are determined from the curve data.
[0019] The volume resistivity of magnetic particles is 1×10 5 Ω cm or more 1×10 9 Ω cm or less is preferable, and 1×10 7 Ω cm or more 1×10 9 Ω·cm or less is more preferable. The volume resistivity (Ω·cm) of magnetic particles is measured as follows: 2 The object to be measured is placed flat on the surface of the circular jig on which the electrode plate is arranged, with a thickness of 1 mm to 3 mm, to form a layer. 2 The layer is sandwiched between two electrode plates. In order to eliminate any gaps between the objects being measured, a 4 kg load is placed on the electrode plates placed on the layer, and then the layer thickness (cm) is measured. Both electrodes above and below the layer are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to both electrodes so that the electric field is 103.8 V / cm, and the current value (A) that flows at this time is read. The measurement environment is a temperature of 20°C and a relative humidity of 50%. The formula for calculating the volumetric electrical resistivity (Ω·cm) of the object being measured is as shown below. R = E × 20 / (II 0 ) / L In the above formula, R is the volume resistivity of the object to be measured (Ω cm), E is the applied voltage (V), I is the current value (A), and I 0 is the current value (A) at an applied voltage of 0 V, and L is the layer thickness (cm). The coefficient 20 is the area of the electrode plate (cm 2 )
[0020] (Resin layer) -Resin that composes the resin layer- The resin layer contains a resin that constitutes the resin layer. Examples of resins that make up the resin layer include styrene-acrylic acid copolymers; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymers; straight silicone resins or modified products thereof consisting of organosiloxane bonds; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyesters; polyurethanes; polycarbonates; amino resins such as urea-formaldehyde resins; and epoxy resins.
[0021] The resin layer preferably contains an acrylic resin having an alicyclic structure. As a polymerization component of the acrylic resin having an alicyclic structure, a lower alkyl ester of (meth)acrylic acid (for example, an alkyl (meth)acrylate ester having an alkyl group with 1 to 9 carbon atoms) is preferable, and specific examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These monomers may be used alone or in combination of two or more. The acrylic resin having an alicyclic structure preferably contains cyclohexyl (meth)acrylate as a polymerization component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the acrylic resin having an alicyclic structure is preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less, based on the total mass of the acrylic resin having an alicyclic structure.
[0022] The thickness of the resin layer is preferably 0.3 μm or more and 3.0 μm or less, more preferably 0.4 μm or more and 2.0 μm or less, and even more preferably 0.5 μm or more and 1.5 μm or less.
[0023] By setting the thickness of the resin layer within the above range, the wear resistance of the carrier is more likely to be improved, and therefore the carrier can be more effectively prevented from having missing images when a high density image is formed under a high temperature and high humidity environment after successively forming low density images under a high temperature and high humidity environment.
[0024] The thickness of the resin layer is determined by the following method. The carrier is embedded in epoxy resin and cut with a microtome to prepare a cross section of the carrier. The SEM images of the carrier cross section taken with a scanning electron microscope (SEM) are imported into an image processing analyzer and analyzed. The thickness (μm) of the resin layer is measured at 10 randomly selected locations per carrier particle, and then measurements are taken for 100 carriers, and the arithmetic average of all measurements is calculated, which is the film thickness (μm) of the resin layer.
[0025] The content of the resin constituting the resin layer is preferably 50% by mass or more and 100% by mass or less, more preferably 52% by mass or more and 98% by mass or less, and even more preferably 55% by mass or more and 95% by mass or less, based on the entire resin layer.
[0026] -Silica particles- The resin layer contains silica particles. Examples of the silica particles include dry silica particles and wet silica particles. Examples of dry silica particles include combustion silica (fumed silica) obtained by burning a silane compound, and deflagration silica obtained by explosively burning metallic silicon powder. Examples of wet silica particles include wet silica particles obtained by a neutralization reaction between sodium silicate and a mineral acid (precipitation method silica synthesized and agglomerated under alkaline conditions, gel method silica particles synthesized and agglomerated under acidic conditions), colloidal silica particles (silica sol particles) obtained by making acidic silicic acid alkaline and polymerizing it, and sol-gel method silica particles obtained by hydrolysis of an organic silane compound (e.g., alkoxysilane). Among these, wet silica particles are preferred as the silica particles.
[0027] The average particle size of the silica particles is 50 nm or more and 200 nm or less. From the viewpoint of obtaining a carrier that can better suppress the occurrence of image voids when a high-density image is formed in a high-temperature, high-humidity environment after successively forming low-density images in a high-temperature, high-humidity environment, the average particle size of the silica particles is preferably 50 nm or more and 200 nm or less, more preferably 53 nm or more and 180 nm or less, and even more preferably 55 nm or more and 150 nm or less.
[0028] The average particle size of the silica particles is measured as follows. The carrier is embedded in epoxy resin and cut with a microtome to prepare a cross section of the carrier. The SEM image of the carrier cross section taken with a scanning electron microscope (SEM) is imported into an image processing analyzer and subjected to image analysis. 100 silica particles (primary particles) are randomly selected from the resin layer, and the circle equivalent diameter (nm) of each is calculated and the arithmetic average is calculated, which is the average particle diameter (nm) of the silica particles.
[0029] The surface of the silica particles may be subjected to hydrophobic treatment. Examples of the hydrophobic treatment agent include known organosilicon compounds having an alkyl group (e.g., methyl group, ethyl group, propyl group, butyl group, etc.), and specific examples include alkoxysilane compounds, siloxane compounds, and silazane compounds. Among these, the hydrophobic treatment agent is preferably a silazane compound, and hexamethyldisilazane is preferable. The hydrophobic treatment agent may be used alone or in combination of two or more kinds.
[0030] Examples of methods for hydrophobizing silica particles with a hydrophobizing agent include a method in which supercritical carbon dioxide is used to dissolve the hydrophobizing agent in supercritical carbon dioxide and adhere the hydrophobizing agent to the surfaces of inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is applied (e.g., sprayed or coated) to the surfaces of inorganic particles in the atmosphere to adhere the hydrophobizing agent to the surfaces of inorganic particles; and a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is added to an inorganic particle dispersion in the atmosphere, the solution is maintained, and then the mixed solution of the inorganic particle dispersion and the solution is dried.
[0031] -Conductive materials- The resin layer may include a conductive material. Examples of conductive materials include metals such as carbon black, gold, silver, and copper, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, potassium titanate, tin oxide, antimony-doped tin oxide, tin-doped indium oxide, aluminum-doped zinc oxide, and resin particles coated with metals.
[0032] The content of the conductive material is preferably from 0% by mass to 10% by mass, and more preferably from 0.05% by mass to 5% by mass, based on the entire resin layer.
[0033] -Resin particles- The resin layer may contain resin particles. Examples of the resin particles include thermosetting resin particles and crosslinked resin particles. The thermosetting resin particles are not particularly limited as long as they are particles formed from a thermosetting resin, but particles formed from a resin containing a nitrogen element are preferred. Among them, melamine resin, urea resin, urethane resin, guanamine resin, and amide resin are preferred because they have high positive charging properties and high resin hardness, and therefore the decrease in the charge amount due to peeling of the resin layer is suppressed.
[0034] As the thermosetting resin particles, commercially available products can be used, such as Eposta S (made by Nippon Shokubai Co., Ltd., melamine-formaldehyde condensation resin) and Eposta MS (made by Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensation resin).
[0035] The content of the conductive material is preferably from 0% by mass to 10% by mass, and more preferably from 0.05% by mass to 5% by mass, based on the entire resin layer.
[0036] (Carrier characteristics) -Si element ratio- The ratio Si1 of Si elements in a region from the surface of the resin layer toward the inside of the resin layer at a distance of 0.1 μm or more and 0.2 μm or less, and the ratio Si2 of Si elements in a region from the surface of the magnetic particle toward the surface of the resin layer at a distance of 0.0 μm or more and 0.1 μm or less satisfy the following formulas 1-1 and 2-1. Formula 1-1: 0.005≦Si1≦2 Formula 2-1:1≦Si1 / Si2≦1000
[0037] Here, by satisfying formula 2-1, a large amount of silica particles are contained in the region close to the surface of the resin layer of the carrier. This improves the wear resistance of the carrier. Also, by satisfying formula 2-1, the amount of silica particles near the surface of the magnetic particles of the carrier is small. This improves the adhesion of the resin layer to the magnetic particles, and makes it easier to improve the wear resistance of the carrier.
[0038] From the viewpoint of obtaining a carrier that can further suppress the occurrence of image voids when a high-density image is formed under a high-temperature, high-humidity environment after successively forming low-density images under a high-temperature, high-humidity environment, the ratios Si1 and Si2 preferably satisfy the following formulas 1-2 and 2-2, more preferably satisfy the following formulas 1-3 and 2-3, and further preferably satisfy the following formulas 1-4 and 2-4.
[0039] Formula 1-2: 0.01≦Si1≦1 Formula 2-2: 50≦Si1 / Si2≦400
[0040] The ratios Si1 and Si2 are measured as follows. Etching is performed from the carrier surface toward the inside in 150 nm increments, and the proportion of Si element on the surface after etching is measured by XPS (X-ray photoelectron spectroscopy). Note that etching and XPS measurement are performed until the magnetic particle surface is reached. The arithmetic mean value of the proportion of Si element measured in a region from the surface of the resin layer to the inside at a distance of 0.1 μm to 0.2 μm is defined as the proportion Si1. The arithmetic mean value of the proportion of Si element measured in a region from the surface of the magnetic particle to the surface of the resin layer at a distance of 0.0 μm to 0.1 μm is defined as the proportion Si2.
[0041] The proportion of Si element is measured by XPS as follows. An X-ray photoelectron spectroscopy (XPS) analyzer (JPS-9000MX manufactured by JEOL Ltd.) is used, and MgKα radiation is used as the X-ray source, with the acceleration voltage set to 20 kV and the emission current set to 10 mA, and the number of each atom is calculated based on the measured carbon, oxygen, and silicon spectra. The atomic weight of silicon relative to the total atomic weight of carbon, oxygen, and silicon in the measurement area is calculated, and this value is taken as the ratio of Si element.
[0042] The etching method will also be described. Specifically, a 6 mm square area of the resin layer is etched using an argon gas cluster ion gun. -Etching conditions- Etching gun: Argon gas cluster ion gun Vacuum degree: (3±1)×10 -2 Pa Measurement intensity: 400 eV, 6 mA Sweep area: 6mm x 6mm
[0043] -Volume average particle size- The volume average particle diameter of the carrier is 20 μm or more and 50 μm or less. From the viewpoint of further suppressing the occurrence of uneven image density when a high-density image is formed in a high-temperature, high-humidity environment after successively forming low-density images in a high-temperature, high-humidity environment, the volume average particle size of the carrier is preferably 23 μm or more and 47 μm or less, more preferably 25 μm or more and 45 μm or less, and even more preferably 27 μm or more and 43 μm or less.
[0044] The volume average particle diameter of the carrier is measured as follows. A Coulter Multisizer II (manufactured by Beckman Coulter) is used as the measuring device, and ISOTON-II (manufactured by Beckman Coulter) is used as the electrolyte. First, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% by mass aqueous solution of a surfactant, preferably sodium alkylbenzene sulfonate, as a dispersant, and this is added to 100 ml to 150 ml of the electrolyte. The electrolyte in which the measurement sample is suspended is dispersed for about 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a particle size range of 2.0 μm to 60 μm is measured using the Coulter Multisizer II with an aperture with an aperture diameter of 100 μm. The number of particles to be measured is 50,000. The measured particle size distribution is divided into particle size ranges (channels), and a cumulative distribution is drawn for the volume from the small particle size side. The particle size at which the cumulative 50% occurs is called the volume average particle size (D 50v ) is defined as
[0045] (Carrier Manufacturing Method) The method for producing the carrier used in the present embodiment is not particularly limited as long as it is a method capable of forming the carrier used in the present embodiment. An example of the method for producing the carrier of the present embodiment will be described below.
[0046] The carrier of this embodiment can be manufactured by, for example, an immersion method in which magnetic particles are immersed in a resin layer forming solution, a spray method in which the resin layer forming solution is stirred and dispersed using a stirring device (e.g., a sand mill, etc.) and sprayed onto the surfaces of the magnetic particles, a fluidized bed method in which the resin layer forming solution is sprayed on the magnetic particles while suspended in flowing air, or a kneader coater method in which the resin layer forming solution and magnetic particles are mixed in a kneader coater and then the solvent is removed. Alternatively, a method may be used in which a particulate resin is used without using a solvent, and the particulate resin is attached to a core material and melted by heating to produce a carrier. A dry coating method includes a powder coating method in which coated resin particles and core particles are coated by heating or mixing them at high speed.
[0047] The method for producing the carrier of this embodiment is preferably a kneader coater method from the viewpoint of setting the ratio Si1 and the ratio Si2 within the desired range.
[0048] The method for producing the carrier of this embodiment is as follows: a first step of mixing a resin layer forming solution A and magnetic particles in a kneader coater, and then removing the solvent to obtain a first coated carrier; a second step of mixing the resin layer forming solution B and the first coated carrier in a kneader coater, and then removing the solvent to obtain a carrier; It is preferred that the compound contains
[0049] -1st process- The resin layer forming solution A preferably contains, for example, a resin constituting the resin layer, a solvent, and silica particles. The content of the resin constituting the resin layer contained in the resin layer forming solution A is preferably 10% by mass or more and 30% by mass or less with respect to the entire solution. The content of the silica particles contained in the resin layer forming solution A is preferably 0.001% by mass or more and 0.01% by mass or less with respect to the entire solution.
[0050] The amount of resin layer forming solution A added in the first step is preferably such that the solid content of resin layer forming solution A is 0.5 parts by mass or more and 1.5 parts by mass or less per 100 parts by mass of the magnetic particles.
[0051] -Second process- The resin layer forming solution B preferably contains, for example, a resin constituting the resin layer, a solvent, and silica particles. The content of the resin constituting the resin layer contained in the resin layer forming solution B is preferably 10% by mass or more and 30% by mass or less with respect to the entire solution. The content of the silica particles contained in the resin layer forming solution B is preferably 0.1% by mass or more and 1.0% by mass or less with respect to the entire solution. The content of silica particles contained in the resin layer forming solution B is preferably greater than the content of silica particles contained in the resin layer forming solution A. By doing so, the obtained carrier is more likely to have the Si element ratio Si1 and the Si element ratio Si2 satisfying the formula 1-1 and the formula 2-1.
[0052] The amount of resin layer forming solution B added in the second step is preferably 1.5 parts by mass or more and 2.5 parts by mass or less in terms of solid content per 100 parts by mass of the first coated carrier.
[0053] The solvent used in the resin layer forming solution is not particularly limited as long as it dissolves the resin, but examples of the solvent that can be used include aromatic hydrocarbons such as xylene and toluene, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran and dioxane, and halides such as chloroform and carbon tetrachloride.
[0054] A sieving step for removing coarse particles may be included after each of the first and second steps.
[0055] In this embodiment, the method for producing the magnetic particles is not particularly limited, but an example of the method will be described.
[0056] The magnetic particles are manufactured, for example, according to the following general manufacturing method of ferrite core particles. Appropriate amounts of each oxide are mixed, water is added, and the mixture is ground and mixed in a wet ball mill or wet vibration mill for, for example, 1 hour or more, preferably 1 hour to 20 hours. The slurry thus obtained is dried and further ground, and then pre-fired at a temperature of, for example, 700°C to 1200°C. After pre-fire, the mixture is further ground in a wet ball mill or wet vibration mill to obtain a mixed powder with a particle size of 1 μm or less. The obtained mixed powder is granulated by a granulating means such as a spray dryer, and the mixture is held at a temperature of, for example, 1000°C to 1500°C for 1 hour to 24 hours, and then fired.
[0057] In this embodiment, the particle size of the mixed powder obtained by pulverizing the powder in a mill or the like after calcination, as well as the arithmetic surface roughness Ra of the surfaces of the obtained magnetic particles, are controlled by adjusting the granulation method and the calcination temperature.
[0058] As the raw material of the magnetic particles, any known material may be used, but ferrite or magnetite is preferably selected. As another raw material, for example, iron powder is known. Since iron powder has a large specific gravity and is prone to deteriorating the toner, ferrite and magnetite are more stable. As an example of ferrite, which is a raw material composition of the magnetic particles, ferrite generally represented by the following formula can be given.
[0059] (MO) X (Fe 2 O 3 ) Y (In the formula, M contains at least one selected from Cu, Zn, Fe, Mg, Mn, Li, Ti, Ni, Sn, Sr, Si, Al, Ba, Co, Mo, Ca, etc., and X and Y represent a molar mass ratio and satisfy the condition X+Y=100.)
[0060] <Electrostatic image developer> The electrostatic image developer according to this embodiment is configured as a two-component developer containing the carrier according to this embodiment and a toner for developing electrostatic images (hereinafter, also simply referred to as "toner"). In the two-component developer, the mixing ratio (mass ratio) of the toner and the carrier is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100. The toner used in the electrostatic image developer according to this embodiment will be described below.
[0061] (Toner for developing electrostatic images) The toner for developing electrostatic images according to the present embodiment (hereinafter, also simply referred to as toner) contains toner particles and, if necessary, an external additive. The toner particles are configured to contain, for example, a binder resin, and, if necessary, a colorant, a release agent, and other additives. The binder resin, colorant, release agent, other additives, and external additives contained in the toner particles are not particularly limited, and may be any of the conventionally known additives used in toner.
[0062] (Characteristics of toner particles, etc.) The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that coats the core portion. Here, the toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer containing the binder resin.
[0063] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0064] The various average particle sizes and particle size distribution indexes of the toner particles are measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each divided particle size range (channel) from the smallest diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the volume average particle size D50v, the cumulative number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and number particle size D84p. Using these, the volumetric particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as:
[0065] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.
[0066] The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 3,500. When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.
[0067] (Toner manufacturing method) Next, a method for producing the toner according to the present embodiment will be described. The toner according to the exemplary embodiment is obtained by producing toner particles and then externally adding an external additive to the toner particles.
[0068] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation-coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). The method for producing the toner particles is not particularly limited, and a well-known production method is adopted. Among these, it is preferable to obtain toner particles by the aggregation and coalescence method.
[0069] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, The toner particles are manufactured through a process including a step of preparing a resin particle dispersion in which resin particles to be a binder resin are dispersed (resin particle dispersion preparation process), a step of aggregating the resin particles (or other particles, if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation process), and a step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, fusing and coalescing the aggregated particles, and forming toner particles (fusion and coalescence process).
[0070] The toner according to the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.
[0071] <Image forming device / image forming method> An image forming apparatus / image forming method according to this embodiment will be described. The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.
[0072] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0073] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is then secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder before charging after the transfer of the toner image; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it before charging after the transfer of the toner image. In the case of an intermediate transfer type device, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.
[0074] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a developing means that contains the electrostatic image developer according to the present embodiment is preferably used.
[0075] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.
[0076] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 1 includes first to fourth electrophotographic image forming units 10Y, 10M, 10C, and 10K (image forming means) that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachable from the image forming apparatus.
[0077] Above each of the units 10Y, 10M, 10C, and 10K in the drawing, an intermediate transfer belt 20 is provided as an intermediate transfer body extending through each unit. The intermediate transfer belt 20 is provided wound around a drive roll 22 and a support roll 24 that are arranged from left to right in the drawing at a distance from each other and contact the inner surface of the intermediate transfer belt 20, and is adapted to run in a direction from the first unit 10Y to the fourth unit 10K. Note that a force is applied to the support roll 24 in a direction away from the drive roll 22 by a spring or the like (not shown), and tension is applied to the intermediate transfer belt 20 wound around them. In addition, an intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. Further, the developing devices (developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with toner including four colors of toner, yellow, magenta, cyan, and black, contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.
[0078] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative example. Note that by assigning reference numerals of magenta (M), cyan (C), and black (K) instead of yellow (Y) to parts equivalent to those of the first unit 10Y, descriptions of the second to fourth units 10M, 10C, and 10K will be omitted.
[0079] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20 and is provided at a position facing the photoconductor 1Y. Furthermore, a bias power supply (not shown) that applies a primary transfer bias is connected to each of the primary transfer rolls 5Y, 5M, 5C, and 5K. Each bias power supply varies the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).
[0080] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity at 20° C. of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam 3Y, the resistivity of the portion irradiated with the laser beam changes. A laser beam 3Y is output to the charged surface of the photoreceptor 1Y via an exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). The laser beam 3Y is irradiated onto the photosensitive layer on the surface of the photoreceptor 1Y, and an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0081] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y is rotated to a predetermined developing position as the photoconductor 1Y travels. Then, at this developing position, the electrostatic image on the photoconductor 1Y is made visible as a toner image (developed image) by the developing device 4Y.
[0082] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.
[0083] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and in the first unit 10Y, for example, it is controlled to +10 μA by a control unit (not shown). On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.
[0084] Further, the primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of the respective colors are transferred in a superimposed manner.
[0085] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.
[0086] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.
[0087] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets, etc. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with resin or the like, art paper for printing, etc. are preferably used.
[0088] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.
[0089] <Process cartridge / toner cartridge> The process cartridge according to this embodiment will be described. The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.
[0090] In addition, the process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing device and, as necessary, at least one other means selected from an image carrier, a charging means, an electrostatic image forming means, and a transfer means.
[0091] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.
[0092] FIG. 2 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 2 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 2, 109 denotes an exposure device (an example of an electrostatic image forming means), 112 denotes a transfer device (an example of a transfer means), 115 denotes a fixing device (an example of a fixing means), and 300 denotes recording paper (an example of a recording medium).
[0093] Next, the toner cartridge according to this embodiment will be described. The toner cartridge according to the present embodiment is a toner cartridge that contains the toner according to the present embodiment and is detachably attached to an image forming apparatus. The toner cartridge contains replenishment toner to be supplied to a developing unit provided in the image forming apparatus.
[0094] 1 is an image forming apparatus having a configuration in which toner cartridges 8Y, 8M, 8C, and 8K can be attached and detached, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) through toner supply pipes (not shown). When the toner contained in the toner cartridge becomes low, the toner cartridge is replaced. EXAMPLES
[0095] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0096] <Toner Production> (Preparation of amorphous polyester resin dispersion (A1)) Ethylene glycol: 37 parts Neopentyl glycol: 65 parts 1,9-nonanediol: 32 parts Terephthalic acid: 96 parts The above materials were charged in a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was stirred uniformly, 1.2 parts of dibutyltin oxide were added. The temperature was raised to 240°C over 6 hours while distilling off the water produced, and stirring was continued at 240°C for 4 hours to obtain an amorphous polyester resin (acid value 9.4 mgKOH / g, weight average molecular weight 13,000, glass transition temperature 62°C). The amorphous polyester resin was transferred to an emulsifier / disperser (Cavitron CD1010, Eurotech) in a molten state at a rate of 100 g per minute. Separately, a dilute ammonia water with a concentration of 0.37% obtained by diluting reagent ammonia water with ion-exchanged water was placed in a tank, and the dilute ammonia water was transferred to the emulsifier / disperser at a rate of 0.1 liters per minute simultaneously with the amorphous polyester resin while being heated to 120°C with a heat exchanger. The emulsifier / disperser was operated at a rotor rotation speed of 60Hz and a pressure of 5kg / cm. 2 By operating under the above conditions, a non-crystalline polyester resin dispersion (A1) having a volume average particle size of 160 nm and a solid content of 20% was obtained.
[0097] [Preparation of crystalline polyester resin dispersion (C1)] Decanedioic acid: 81 parts Hexanediol: 47 parts The above materials were charged into a flask, and the temperature was raised to 160°C over 1 hour. After confirming that the reaction system was stirred uniformly, 0.03 parts of dibutyltin oxide was added. The temperature was raised to 200°C over 6 hours while distilling off the water produced, and stirring was continued at 200°C for 4 hours. The reaction liquid was then cooled, solid-liquid separation was performed, and the solid matter was dried at a temperature of 40°C under reduced pressure to obtain a crystalline polyester resin (C1) (melting point 64°C, weight average molecular weight 15,000).
[0098] Crystalline polyester resin (C1): 50 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 2 parts - Ion-exchanged water: 200 parts The above materials were heated to 120°C, thoroughly dispersed using a homogenizer (Ultra Turrax T50, IKA), and then dispersed using a pressure discharge homogenizer. When the volume average particle size reached 180 nm, the particles were collected to obtain a crystalline polyester resin dispersion (C1) with a solid content of 20%.
[0099] [Preparation of release agent particle dispersion (W1)] Paraffin wax (HNP-9, manufactured by Nippon Seiro Co., Ltd.): 100 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 1 part Ion-exchanged water: 350 parts The above materials were mixed and heated to 100°C, dispersed using a homogenizer (IKA Ultra Turrax T50), and then dispersed using a pressure discharge Gaulin homogenizer to obtain a release agent particle dispersion in which release agent particles with a volume average particle size of 200 nm were dispersed. Ion-exchanged water was added to this release agent particle dispersion to adjust the solid content to 20%, and this was used as release agent particle dispersion (W1).
[0100] [Preparation of colorant particle dispersion (Y1)] Yellow pigment (CI Pigment Yellow 180): 50 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts Ion-exchanged water: 195 parts The above materials were mixed and dispersed for 60 minutes using a high-pressure impact disperser (Ultimaizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (K1) with a solid content of 20%.
[0101] [Preparation of colorant particle dispersion (C1)] Cyan pigment (Pigment Blue 15:3, Dainichi Seika Color & Chemicals): 50 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts Ion-exchanged water: 195 parts The above materials were mixed and dispersed for 60 minutes using a high-pressure impact disperser (Ultimaizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (C1) with a solid content of 20%.
[0102] [Preparation of colorant particle dispersion (M1)] Magenta pigment (Pigment Red 122, DIC): 50 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts Ion-exchanged water: 195 parts The above materials were mixed and dispersed for 60 minutes using a high-pressure impact disperser (Ultimaizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (M1) with a solid content of 20%.
[0103] [Preparation of Yellow Toner Particles (Y1)] - Ion-exchanged water: 200 parts Amorphous polyester resin dispersion (A1): 150 parts Crystalline polyester resin dispersion (C1): 10 parts Release agent particle dispersion (W1): 10 parts Colorant particle dispersion (Y1): 15 parts Anionic surfactant (TaycaPower): 2.8 parts The above materials were placed in a round stainless steel flask, and 0.1N nitric acid was added to adjust the pH to 3.5, and then an aqueous solution of polyaluminum chloride in which 2 parts of polyaluminum chloride (Oji Paper Co., Ltd., 30% powder product) were dissolved in 30 parts of ion-exchanged water was added. After dispersion at 30°C using a homogenizer (IKA Ultra Turrax T50), the mixture was heated to 45°C in a heating oil bath and held until the volume average particle size became 4.9 μm. Next, 60 parts of amorphous polyester resin dispersion (A1) was added and held for 30 minutes. Next, when the volume average particle size became 5.2 μm, 60 parts of amorphous polyester resin dispersion (A1) was further added and held for 30 minutes. Next, 20 parts of a 10% NTA (nitrilotriacetic acid) metal salt aqueous solution (Chilest 70, Chelest Co., Ltd.) was added, and a 1N aqueous solution of sodium hydroxide was added to adjust the pH to 9.0. Next, 1 part of anionic surfactant (TaycaPower) was added, and the mixture was heated to 85° C. while continuing to stir, and maintained at that temperature for 5 hours. The mixture was then cooled to 20° C. at a rate of 20° C. / min. The mixture was then filtered, thoroughly washed with ion-exchanged water, and dried to obtain yellow toner particles (Y1) having a volume average particle size of 5.7 μm and an average circularity of 0.971.
[0104] [Preparation of cyan toner particles (C1)] Cyan toner particles (C1) were obtained in the same manner as in the preparation of yellow toner particles (Y1), except that the colorant particle dispersion liquid (Y1) was changed to the colorant particle dispersion liquid (C1).
[0105] [Preparation of magenta toner particles (M1)] Magenta toner particles (M1) were obtained in the same manner as in the preparation of yellow toner particles (Y1), except that the colorant particle dispersion liquid (Y1) was changed to the colorant particle dispersion liquid (M1).
[0106] [Toner production] By adding external additives to each toner particle, a yellow toner (Y1), a cyan toner (C1), and a magenta toner (M1) were obtained.
[0107] <Ferrite particles> (Preparation of Ferrite Particles (1)) Fe 2 O 3 1318 parts and Mn(OH) 2 587 parts and Mg(OH) 2 The mixture was mixed with 96 parts of polyvinyl alcohol and 0.5 parts of polycarboxylic acid as a dispersant, and zirconia beads with a media diameter of 1 mm were added to water, and the mixture was ground and mixed in a sand mill for 30 minutes to obtain a dispersion. The volume average particle size of the particles in the dispersion was 1.5 μm. The dispersion liquid was used as a raw material, and granulated and dried using a spray dryer to obtain granules with a volume average particle size of 35 μm. Next, in an oxygen-nitrogen mixed atmosphere with an oxygen partial pressure of 1%, main sintering was performed using an electric furnace at a temperature of 1350°C for 4 hours, and then heating was performed in the air at a temperature of 900°C for 3 hours to obtain sintered particles. The sintered particles were crushed and classified to obtain ferrite particles (1) with a volume average particle size of 35 μm. The arithmetic surface roughness Ra (JIS B0601:2001) of the surface of the ferrite particles (1) was 0.7 μm.
[0108] (Preparation of ferrite particles (2)) In the main firing step, ferrite particles (2) having a volume average particle size of 35 μm were obtained by preparing them in the same manner as ferrite particles 1, except that the firing temperature was 1400° C. and the firing time was 6 hours. The arithmetic surface roughness Ra (JIS B0601:2001) of the surface of the ferrite particles (2) was 0.5 μm. (Preparation of ferrite particles (3)) Ferrite particles (3) having a volume average particle size of 35 μm were obtained by preparing them in the same manner as ferrite particles 1, except that the sand milling time was extended to 1 hour and the volume average particle size of the particles in the dispersion was set to 1.0 μm. The arithmetic surface roughness Ra (JIS B0601:2001) of the surface of the ferrite particles (3) was 1.1 μm.
[0109] <Silica particles> (Preparation of Silica Particles (1)) Commercially available silica particles (spherical sol-gel silica, X24-9163A manufactured by Shin-Etsu Chemical Co., Ltd., average particle size 120 nm) were prepared and designated as silica particles (1).
[0110] (Preparation of Silica Particles (2)) Commercially available silica particles (fumed silica, Silfil NHM-4N, average particle size 90 nm, manufactured by Tokuyama Corporation) were prepared and designated as silica particles (2).
[0111] (Preparation of Silica Particles (3)) Commercially available silica particles (spherical sol-gel silica, Cabot Corporation, TG-C413, average particle size 50 nm) were prepared and designated as silica particles (3). (Preparation of Silica Particles (4)) Commercially available silica particles (spherical sol-gel silica, Cabot Corporation TG-C6020, average particle size 200 nm) were prepared and designated as silica particles (4). (Preparation of Silica Particles (5)) Commercially available silica particles (fumed silica, Cabot Corporation, TG-3110, average particle size 12 nm) were prepared and designated as silica particles (5).
[0112] [Silica particles (6)] [Preparation of silica particles (6)] - Preparation process [Preparation of alkaline catalyst solution] - 200 parts of methanol and 36 parts of 10% aqueous ammonia were placed in a glass reaction vessel equipped with a stirring blade, a dropping nozzle, and a thermometer, and mixed with stirring to obtain an alkaline catalyst solution. The ammonia content of the alkaline catalyst solution was 0.73 mol / L. -Particle generation process [Preparation of silica particle suspension]- (granulation process) The temperature of the alkaline catalyst solution was adjusted to 50° C., and the alkaline catalyst solution was replaced with nitrogen. Thereafter, while stirring the alkaline catalyst solution at 120 rpm, tetramethoxysilane (TMOS) and ammonia water with a concentration of 3.7% were dropped at flow rates of 4 parts / min and 2.4 parts / min, respectively. After 2 minutes had elapsed since the start of the supply of tetramethoxysilane and aqueous ammonia, the supply of tetramethoxysilane and aqueous ammonia was stopped at the same time. The amount of tetramethoxysilane supplied at the time of stopping the supply of tetramethoxysilane and aqueous ammonia was 0.0063 mol / mol relative to the number of moles of alcohol added to the reaction vessel in the preparation step. After the supply of tetramethoxysilane and aqueous ammonia was stopped, the mixture was stirred for 10 minutes, and then the supply of tetramethoxysilane and aqueous ammonia was resumed. The flow rates of tetramethoxysilane and aqueous ammonia were set to 4 parts / min and 2.4 parts / min, respectively. The amounts of tetramethoxysilane and 3.7% aqueous ammonia added in all steps including the first supplying step and the second supplying step were 90 parts of tetramethoxysilane and 54 parts of 3.7% aqueous ammonia. After the dropwise addition of tetramethoxysilane and 3.7% aqueous ammonia was completed, a suspension of silica particles was obtained. (Solvent removal, drying) The solvent in the obtained silica particle suspension was heated and distilled to remove 150 parts of the solvent, followed by adding 150 parts of pure water and drying with a freeze dryer to obtain silica particles before hydrophobization treatment. -Hydrophobic treatment of silica particles- 7 parts of hexamethyldisilazane was added to 35 g of silica particles before hydrophobization treatment, and the mixture was reacted at 150° C. for 2 hours to obtain silica particles (silica particles (6)) whose surfaces had been hydrophobized. The volume average particle size of the obtained silica particles (6) was measured and found to be 220 nm.
[0113] <Example 1> (Creating the carrier) -1st process- Cyclohexyl methacrylate / methyl methacrylate copolymer (copolymerization ratio 95 mol:5 mol) 1 part Silica particles (1) 0.0005 parts Toluene 5 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were put into a sand mill and stirred at a rotation speed of 1200 rpm for 30 minutes to obtain a resin layer forming solution (1). 100 parts of ferrite particles (1) were placed in a vacuum degassing kneader, and then the resin layer forming solution (1) was added, and the mixture was heated and decompressed for 30 minutes while stirring at 40 rpm, and the toluene was distilled off to coat the ferrite particles (1) with resin. Then, fine and coarse powders were removed with an elbow jet to obtain a first coated carrier (1).
[0114] -Second process- Cyclohexyl methacrylate / methyl methacrylate copolymer (copolymerization ratio 95 mol:5 mol) 2 parts Silica particles (1) 0.05 parts Toluene 10 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 1200 rpm for 30 minutes to prepare a resin layer forming solution (2). The resin-coated carrier (2) was placed in a vacuum degassing kneader, and the resin layer forming solution (2) was then added, and the mixture was heated and decompressed for 30 minutes while stirring at 40 rpm. Then, fine and coarse powders were removed using an elbow jet to obtain a carrier (1).
[0115] (Preparation of developer) The carrier (1) and the yellow toner (Y1) were placed in a V blender in a mixing ratio of carrier:toner=100:10 (mass ratio) and stirred for 20 minutes to obtain a yellow developer. A cyan developer was obtained in the same manner as above, except that the yellow toner (Y1) was replaced with a cyan toner (C1). A magenta developer was obtained in the same manner as above, except that the yellow toner (Y1) was changed to a magenta toner (M1).
[0116] <Example 2> A developer was obtained in the same manner as in Example 1, except that in the second step of the carrier production method, the amount of silica particles (1) added was 0.005 part.
[0117] <Example 3> A developer was obtained in the same manner as in Example 1, except that in the second step of the carrier production method, the amount of silica particles (1) added was 0.1 part.
[0118] <Example 4> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.005 parts, and the amount of silica particles (1) added in the second step of the carrier manufacturing method was 0.005 parts.
[0119] <Example 5> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.0001 parts, and the amount of silica particles (1) added in the second step of the carrier was 0.1 parts.
[0120] <Example 6> A developer was obtained in the same manner as in Example 1, except that in the production method of the carrier, silica particles (2) were used instead of silica particles (1).
[0121] <Example 7> A developer was obtained in the same manner as in Example 1, except that in the production method of the carrier, silica particles (3) were used instead of silica particles (1).
[0122] <Example 8> A developer was obtained in the same manner as in Example 1, except that in the production method of the carrier, silica particles (4) were used instead of silica particles (1).
[0123] <Example 9> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.005 parts, and the amount of silica particles (1) added in the second step of the carrier manufacturing method was 1 part.
[0124] <Example 10> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.005 parts, and the amount of silica particles (1) added in the second step of the carrier manufacturing method was 2 parts.
[0125] <Example 11> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.005 parts, and the amount of silica particles (1) added in the second step of the carrier manufacturing method was 0.006 parts.
[0126] <Example 12> A developer was obtained in the same manner as in Example 1, except that in the second step of the carrier production method, the amount of silica particles (1) added was 0.025 parts.
[0127] <Example 13> A developer was obtained in the same manner as in Example 1, except that in the second step of the carrier production method, the amount of silica particles (1) added was 0.008 part.
[0128] <Example 14> A developer was obtained in the same manner as in Example 1, except that in the second step of the carrier production method, the amount of silica particles (1) added was 0.012 parts.
[0129] <Example 15> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.005 parts, and the amount of silica particles (1) added in the second step of the carrier manufacturing method was 0.9 parts.
[0130] <Example 16> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.005 parts, and the amount of silica particles (1) added in the second step of the carrier manufacturing method was 1.1 parts.
[0131] <Example 17> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.0002 parts, and the amount of silica particles (1) added in the second step of the carrier was 0.07 parts.
[0132] <Example 18> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the first step of the carrier manufacturing method was 0.0001 parts, and the amount of silica particles (1) added in the second step of the carrier manufacturing method was 0.05 parts.
[0133] <Example 19> A developer was obtained in the same manner as in Example 1, except that in the carrier production process, the ferrite particles (1) were replaced with the ferrite particles (2).
[0134] <Example 20> A developer was obtained in the same manner as in Example 1, except that in the carrier production process, the ferrite particles (1) were replaced with the ferrite particles (3).
[0135] <Example 21> A developer was obtained in the same manner as in Example 1, except that in the carrier manufacturing process, the amount of cyclohexyl methacrylate / methyl methacrylate copolymer added in the first carrier process was 0.5 parts, and the amount of cyclohexyl methacrylate / methyl methacrylate copolymer added in the second carrier process was 1 part.
[0136] <Example 22> A developer was obtained in the same manner as in Example 1, except that in the carrier manufacturing process, the amount of cyclohexyl methacrylate / methyl methacrylate copolymer added in the first carrier process was 1 part, and the amount of cyclohexyl methacrylate / methyl methacrylate copolymer added in the second carrier process was 4.5 parts.
[0137] <Comparative Example 1> A developer was obtained in the same manner as in Example 1, except that in the first step of the carrier production process, the amount of silica particles (1) added was 0.1 part.
[0138] <Comparative Example 2> A developer was obtained in the same manner as in Example 1, except that in the first step of the carrier production process, the amount of silica particles (1) added was 0.1 part, and no silica particles were added in the second step.
[0139] <Comparative Example 3> A developer was obtained in the same manner as in Example 1, except that in the first step of the carrier production process, the amount of silica particles (1) added was 0.1 parts, and in the second step, the amount of silica particles (1) added was 0.2 parts.
[0140] <Comparative Example 4> A developer was obtained in the same manner as in Example 1, except that in the production method of the carrier, silica particles (5) were used instead of silica particles (1).
[0141] <Comparative Example 5> A developer was obtained in the same manner as in Example 1, except that in the production method of the carrier, silica particles (6) were used instead of silica particles (1).
[0142] <Comparative Example 6> A developer was obtained in the same manner as in Example 1, except that in the first step of the carrier production process, the amount of silica particles (1) added was 0.1 parts, and in the second step, the amount of silica particles (1) added was 2.5 parts.
[0143] <Comparative Example 7> A developer was obtained in the same manner as in Example 1, except that the amount of silica particles (1) added in the second step of the carrier production process was 0.0001 part.
[0144] <Comparative Example 8> A developer was obtained in the same manner as in Example 1, except that in the first step of the carrier production process, the amount of silica particles (1) added was 0.0001 parts, and in the second step, the amount of silica particles (1) added was 0.11 parts.
[0145] <White spot evaluation> The developer obtained in each example was filled into the developer of a modified "DocuCentreColor400 (manufactured by Fuji Xerox Co., Ltd.)". Using DocuCentreColor400 (manufactured by Fuji Xerox Co., Ltd.) in an environment of 28.5°C and 85% RH, a test was conducted in which 10,000 images with a chart of 1% image density were output over 10 days using A4 size J paper (manufactured by Fuji Xerox Co., Ltd.). After a total of 10,000 sheets were output, 500 images with an image density of 30% were printed, and then A4 size 45 paper (manufactured by Ricoh Co., Ltd., basis weight 52 gsm) was used to print the images with a toner loading amount of 9.8 g / cm. 2 A solid image of the tertiary color (process black) and a toner loading of 6.5 g / cm 2 We printed 10 image samples with patches of the secondary colors. The second image sample (hereinafter simply referred to as the image sample) on which a solid image of the tertiary color and a patch of the secondary color were printed was visually inspected and evaluated for white spots based on the following evaluation criteria. Note that the acceptable range was up to C below. A: There is no problem with the image quality. B: Slight unevenness is observed around the tertiary color patches. C: In addition to the tertiary color, slight unevenness is observed around the secondary color patches. D: White spots are observed in the tertiary color. E: In addition to the tertiary color, white spots are observed around the secondary color patches.
[0146] <Fogging evaluation> The image density E of the background part of the first image sample obtained in the white spot evaluation was measured using an image densitometer X-Rite938 (manufactured by X-Rite Co., Ltd.). The image sample was also visually confirmed. Furthermore, tape transfer evaluation on the photoreceptor was performed. Then, from the image density E of the background portion, visual confirmation, and tape transfer evaluation, fogging was evaluated based on the following evaluation criteria. Note that the acceptable range was up to C below. A: The density E of the background part of the image is less than 0.015, no fog can be detected by visual inspection, and there is no problem with the tape transfer onto the photoconductor or the image quality. B: The density E of the background part of the image is 0.015 or more and less than 0.03, and the fog cannot be determined by visual inspection. There is a slight fog in the tape transfer onto the photoconductor, but the image quality is not affected. C: The density E of the background part of the image is 0.03 or more and less than 0.05, and fog is clearly observed in the tape transfer onto the photoconductor. D: The density E of the background of the image is 0.05 or more, and clear fog is observed on the image.
[0147] <Carrier resistance retention evaluation> After the above white spot evaluation, the developer was removed from the developer of the modified "DocuCentreColor400 (manufactured by Fuji Xerox Co., Ltd.)". The toner was removed from the removed developer with an air blower to remove the carrier (hereinafter referred to as used carrier). The electrical resistance of the carrier was measured using a super insulation meter DSM-8104 manufactured by Hioki E.E.C. Corporation. The electrical resistance of the same carrier (unused) as the carrier used in the production of the removed developer was then measured. The percentage of the electrical resistance of the used carrier relative to the electrical resistance of an unused carrier was calculated, and the carrier resistance retention rate was evaluated according to the following evaluation criteria. A: 90% or more and 100% or less B: 80% or more but less than 90% C: 70% or more but less than 80% D: 65% or more but less than 70% E: Less than 65%
[0148] [Table 1]
[0149] [Table 2]
[0150] From the above results, it can be seen that the carrier of this embodiment suppresses the occurrence of image voids when a high-density image is formed in a high-temperature, high-humidity environment after successively forming low-density images in a high-temperature, high-humidity environment. [Explanation of symbols]
[0151] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 30 Intermediate transfer body cleaning device 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 118 Exposure Aperture 117 Cabinet 200 Process Cartridge 300 Recording paper (an example of a recording medium) P Recording paper (an example of a recording medium)
Claims
1. Magnetic particles; a resin layer that covers the magnetic particles and contains silica particles having an average particle size of 50 nm or more and 200 nm or less, The carrier for developing an electrostatic image has a ratio Si1 of the element Si in a region where the distance from the surface of the resin layer in the inward direction is 0.1 μm or more and 0.2 μm or less, and a ratio Si2 of the element Si in a region where the distance from the surface of the magnetic particle in the surface direction of the resin layer is 0.0 μm or more and 0.1 μm or less, satisfying the following formula 1-2 and formula 2-2: Formula 1-2: 0.01≦Si1≦1 Formula 2-2: 50≦Si1 / Si2≦400
2. 2. The carrier for developing an electrostatic image according to claim 1, wherein the arithmetic surface roughness Ra of the surface of said magnetic particles is in the range of 0.2 [mu]m≦Ra≦2 [mu]m.
3. 3. The carrier for developing an electrostatic image according to claim 1, wherein the average particle size of the silica particles is from 55 nm to 150 nm.
4. 4. The carrier for developing electrostatic images according to claim 1, wherein the resin layer has a thickness of 0.3 μm or more and 3.0 μm or less.
5. 5. An electrostatic image developer comprising the electrostatic image developing carrier according to claim 1 and a toner for developing an electrostatic image.
6. a charging step of charging at least an image carrier; an exposure step of forming an electrostatic latent image on the surface of the image carrier; a developing step of developing the electrostatic latent image formed on the surface of the image carrier with an electrostatic charge image developer to form a toner image; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a transfer receiving material; a fixing step of fixing the toner image, The electrostatic image developer according to claim 5 . Image forming method.
7. An image carrier; A charging means for charging the image carrier; an exposure means for exposing the charged image carrier to light to form an electrostatic latent image on the image carrier; a developing means for developing the electrostatic latent image with an electrostatic charge image developer to form a toner image; a transfer means for transferring the toner image from the image carrier to a transfer medium; A fixing unit for fixing the toner image, The electrostatic image developer according to claim 5 . Image forming device.
Citation Information
Patent Citations
Electrostatic latent image developing carrier, its production, electrostatic latent image developer and image forming method
JP1997319155A
Electrostatic charge image developing carrier, electrostatic charge image developer, process cartridge and image forming apparatus
JP2009217059A
Carrier for developer for developing electrostatic charge image, developer for developing the electrostatic charge image, toner cartridge, process cartridge, and image forming apparatus
JP2011186005A
Carrier for electrostatic latent image developer, two-component developer, container with developer, image forming method and process cartridge
JP2012063438A
Carrier for electrostatic charge image development, developer for electrostatic charge image development, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2013195698A